KARAKTERISTIK IBU BERSALIN DENGAN PERDARAHAN POSTPARTUM DI RSUD BANJARNEGARA PERIODE 2009-2010 - Kusmianti Kusmianti; Prasanti Adriani (Viva Medika, 2010)
Maternal mortality remains a major problem in Indonesia. Maternal Mortality Rate (MMR) in Indonesia is relatively high, in 2009, that is 226 / 100,000live births (KH), and the biggest cause of AKI is postpartum hemorrhage that is equalto 80%. The incidence of postpartum hemorrhage in hospitals Banjarnegara 20092010 will be higher as many as 238 cases compared Purbalingga Hospital. Todetermine the characteristics of the birth mothers with postpartum hemorrhage inBanjarnegara District Hospital 2009-2010. This type of research is quantitative descriptive retrospective approach, andsecondary data types. Samples were taken using a total of 238 respondents sampling.Data collected by the master table. The Postpartum Hemorrhage Figures Genesis 3.9%, based on the age of thegreatest at the age of 20-35 years (72.7%), the smallest age <20 years (13.4%). Theparity parity 2-5 (multiparous) (56.3%), the smallest in the parity grandemultipara(2.1%). Based on the factors causing the biggest caused by a retained placenta at53%, and the smallest is caused by inversio uteri and uterine rupture of 0.4%.The incidence of postpartum hemorrhage of 3.7% - 3.9% of 3138 deliveries, thelargest maternal age 20-35 years of age (72.7%). The maternal parity 2-5(multiparous) (56.3%). And the biggest cause factor caused by retained placenta(53%).Keywords: Maternity, Postpartum Hemorrhage